Effective H₂S control during chemical looping combustion by iron ore modified with alkaline earth metal oxides - Wang, Haiming (2022)
Iron ore (IO) modified with alkaline earth metal (AEM) oxides were developed as oxygen carriers (OCs) for the chemical looping combustion (CLC) of simulated municipal solid waste (MSW) syngas to simultaneously reduce the H2S emission. The AEM oxides, especially BaO, were found to improve the CLC performance of IO greatly due to the formation of AEM ferrites, which promoted the lattice oxygen activity. When using the pristine IO, less than 10% of the input H2S could be removed with the remaining being released from the reactor mainly in the form of SO2. The loadings of CaO and MgO were also found to be ineffective in sulfur removal from the syngas, because the sulfur fixation reactions were kinetically and thermodynamically limited for CaO and MgO, respectively. By contrast, over 60% of the input H2S was effectively retained on the BaO-loaded OC in the form of sulfates/sulfites because of the high reactivity between BaCO3 and H2S in the presence of Fe2O3. This study indicates that the IO loaded with BaO showed superior performance both in CLC of syngas and control of sulfur species, which can be used in the CLC of sulfur containing fuels to realize a cleaner combustion process.